Legal Aspects of Business Protection in Indonesia's Digital Era: Aspek Hukum Dalam Perlindungan Bisnis Era Digital Di Indonesia - Alifia Fisilmi Kaffah; Siti Malikhatun Badriyah (Universitas Islam Indonesia, 2024)
This study examines the role of law in protecting digital-era businesses in Indonesia. Globalization opens up economic opportunities to gain maximum profit by developing businesses in the digital era. However, digital-era businesses are faced with challenges in the form of cyber threats or misuse of digital business activities that can cause losses. In this case, law is needed to protect actors in digital businesses. Law is dynamic and can adapt to the current state of society, including business digitalization. Based on this, this study has a problem formulation, namely